ANALYSIS OF SHARE OWNERSHIP AND THE BOARD OF DIRECTORS ON COMPANY PERFORMANCE IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2016-2020 PERIOD - Sumantri Sumantri; Siti Khusnil Khotimah; Sari Dewi (Universitas Internasional Batam, 2022)
This study aims to identify the relationship between share ownership and the board of directors on company performance. This study uses a profitability ratio policy as the dependent variable. The dependent variable in this study is measured by ROA (Return on Assets) and ROE (Return on Equity). Independent directors, number of directors in a company, family ownership, institutional ownership, foreign ownership, blockholder ownership as a measure of independent variables and leverage ratio, growth opportunities (growth), big 4, dividend payout ratio (dividend payout ratio), company size, company age as control variables. The population data of this study are companies listed on the Indonesia Stock Exchange (IDX), the data taken are company data from 2016 to 2020. The analytical method used is multiple linear regression analysis, while to measure the level of significance used partial test (t) and simultaneous test (f).). Positive effect of independent directors on company performance, negative effect of board size on company performance, positive influence of block ownership on company performance. company performance, positive influence of institutional ownership on company performance, positive influence of foreign ownership on company performance, positive influence of family ownership on company performance. Company performance is measured by the ROA and ROE variables.